2017
DOI: 10.1515/chem-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

‘Capiture’ plants with interesting biological activities: a case to go

Abstract: Abstract:The investigation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Pterocarpus erinaceus contains tannins, flavonoids, phenols and saponins. It has also been confirmed that its stem bark possesses a broad antimicrobial spectrum including Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Candida albicans [27][28][29]. Tittikpina et al [29] isolated four compounds from the plant, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Pterocarpus erinaceus contains tannins, flavonoids, phenols and saponins. It has also been confirmed that its stem bark possesses a broad antimicrobial spectrum including Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Candida albicans [27][28][29]. Tittikpina et al [29] isolated four compounds from the plant, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The plant, 'Pterocarpus erinaceus (Fabaceae)' is a tree found in the most tropical areas of Africa [20,21]. In West Africa, its leaves, stem bark, and roots have been reported as highly use for traditional remedies against inflammation, ulcer, pain in the joints, malaria-fever, and bacterial infections [22].Various scientific studies had confirm Pterocarpus erinaceus ability to exhibit several biological activities as well as identification of several components.…”
Section: Introductionmentioning
confidence: 99%
“…The prioritization process led to highly ranked plants that were further investigated biologically [ 12 ]. Following their footsteps, we have also developed a model to identify the most promising plants from a list of species reported after an ethnobotanical survey for possible treatment of infectious diseases in Togo [ 13 ]. The ethnobotanical study involving a semi-structured individual interview with 53 traditional healers from the Tchamba district of Togo led to identifying 43 different species effective against infectious diseases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following their footsteps, we have also developed a model to identify the most promising plants from a list of species reported after an ethnobotanical survey for possible treatment of infectious diseases in Togo [ 13 ]. The ethnobotanical study involving a semi-structured individual interview with 53 traditional healers from the Tchamba district of Togo led to identifying 43 different species effective against infectious diseases [ 13 , 14 ]. This methodology, named CAPITURE (Computer Aided Products Identification from Traditional Usage Records) method, predicted Pterocarpus erinaceus and Daniellia oliveri as the most promising plants out of 43 plant species employed by traditional healers to treat infectious diseases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation